Swedish Bird Survey: Swedish waterbird census (January) - Fredrik Haas (Lund University, 2024)
The Swedish waterbird census in January (Svensk sjöfågelinventering (januari)) was started in 1967 as part of the international midwinter census of waterbirds coordinated by Wetlands International. The winter count of waterbirds is therefore one of the longest running surveys of Swedish birds. It is a valuable tool for monitoring the changes in the wintering populations of waterbirds in Sweden. It also provides good information of the wintering distribution of most of the species.The Swedish waterbird census (January) is one of several schemes within the Swedish Bird Survey, run by the Department of Biology at Lund University. The surveys are with a few exceptions carried out by volunteer ornithologists. The survey is mainly financed by the Swedish Environmental Protection Agency, but smaller contributions come from the county administrative boards and BirdLife Sverige. The results from the survey are reported to Wetlands International.In this dataset, some information is placed in the table ExtendedMeasurementOrFacts (eMoF), which is part of the Source Archive available to download directly from the dataset’s page on gbif.org. The Source Archive contains the data exactly as uploaded to gbif (verbatim). Should you choose to download the dataset as GBIF Annotated Archive instead, the data has been interpreted and quality controlled by gbif, but, the data in the eMoF will not be included, as the eMoF extension is not yet supported by gbif.
Keywords: Samplingevent; SAMPLING_EVENT; Biological Sciences; Biologi